Continuous Literacy Program For All (CLP FALL) to Strengthen Muslim Students' Literacy Culture at Primary School - Yiyin Isgandi (Journal of English Language Teaching and Islamic Integration, 2018)
The phenomenon of Primary School children is more fun to  play  games  than  reading  and  writing  books.  The  literacy  capability  assessment  of  students  in  Indonesia  by  International  Association  of  Educational  (IAE)  and  Organization  for  Economic  Co-operation  and  Development (OECD) from 2011-2015 still below the everage score as  well  as  the  country  ranking.  In  2015  the  Ministry  of  Education  and  Culture  socializes  the  massive  School  Literacy  Movement  named  Gerakan  Literasi  Sekolah  (GLS).  However  in  fact,  the  majority  of Primary Schools in Indonesia is less sensitive and cannot implement the program well in school. In order to solve the problem, the principal and teachers in the Primary School needs to apply the Continous Literacy Program  for  All  (CLP  FALL)  consistently  and  measurably.  By  using Watson-Guthrie’s behaviorism theory and Piaget’s cognitive theory this program should be applied and developed. The program includes three pahases;  1)  planning,  2)  implementation,  and  3)  evaluation  and development.  The  gradual  implementation  includes  daily,  weekly, monthly,  semester,  and  annual  activities  involving  all  academic members.